2011
DOI: 10.1590/s1516-35982011000100021
|View full text |Cite
|
Sign up to set email alerts
|

Níveis nutricionais de treonina digestível para poedeiras leves no segundo ciclo de produção

Abstract: RESUMO -Com o objetivo de determinar a exigência nutricional de treonina digestível para poedeiras comerciais leves de segundo ciclo de produção (79 a 95 semanas de idade), foi conduzido um experimento com 180 poedeiras Lohmann LSL, distribuídas em cinco dietas (0,380; 0,413; 0,446; 0,479; e 0,512% de treonina digestível), seis repetições e seis aves por unidade experimental. Os níveis de treonina na ração tiveram efeito quadrático sobre o consumo de ração, a conversão alimentar por massa e por dúzia de ovos, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…On the other hand, Schmidt et al (2011) found that the production, weight and mass of eggs were influenced by quadratic levels of threonine in the diet. The threonine requirement for these variables was estimated to be 0.465, 0.445 and 0.459%, corresponding to a daily intake of 455, 433 and 448 mg of threonine bird -1 day -1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Schmidt et al (2011) found that the production, weight and mass of eggs were influenced by quadratic levels of threonine in the diet. The threonine requirement for these variables was estimated to be 0.465, 0.445 and 0.459%, corresponding to a daily intake of 455, 433 and 448 mg of threonine bird -1 day -1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…According to Schmidt et al (2011), the formulation of feeds based on amino acid levels is a widely used concept in poultry nutrition with the aim of reducing the crude protein content in the rations. For Figueiredo et al (2012), the essential amino acid levels in laying rations have important influence on egg size, albumen and yolk deposition, percentage of total solids and internal quality of eggs.…”
Section: Introductionmentioning
confidence: 99%
“…The formulation of diets based on total amino acids can lead to deficiencies and/or excesses in their supply (Kidd, Maynard, & Mullenix, 2021). As a measure to circumvent such a problem, the concept of ideal protein arises, which allows formulations of diets without excesses and deficiencies of essential amino acids (Schmidt et al, 2011).…”
Section: Introductionmentioning
confidence: 99%